2018
DOI: 10.1159/000492873
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ Is Specifically Upregulated on Circulating CD14++ CD16+ and CD14+ CD16++ Monocytes in Patients with Atrial Fibrillation and Severe Atrial Fibrosis

Abstract: Background/Aims: Fibrotic remodeling of the atria plays a key role in the pathogenesis of atrial fibrillation (AF). As little is known about the contribution of circulating monocytes in atrial remodeling and the pathophysiology of AF, we investigated profibrotic factors in different subsets of circulating monocytes obtained from patients with atrial fibrillation undergoing catheter ablation. Methods: A 3D high density voltage mapping was performed in sinus rhythm to evaluate the extent of low-voltage areas (LV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…SPP1 is capable of promoting the expression and activation of transforming growth factor-β 1 (TGF-β1), increasing the production of fibrous matrix proteins in lung cells exposed to multi-walled carbon nanotubes [ 7 ]. TGF-β has been detected to be upregulated in CD14++ CD16+ and CD14+ CD16++ monocytes in patients with atrial fibrillation and severe atrial fibrosis [ 8 ]. Meanwhile, activation of the TGF-β pathway contributes to atrial fibrosis in an atrial fibrillation experimental model and patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…SPP1 is capable of promoting the expression and activation of transforming growth factor-β 1 (TGF-β1), increasing the production of fibrous matrix proteins in lung cells exposed to multi-walled carbon nanotubes [ 7 ]. TGF-β has been detected to be upregulated in CD14++ CD16+ and CD14+ CD16++ monocytes in patients with atrial fibrillation and severe atrial fibrosis [ 8 ]. Meanwhile, activation of the TGF-β pathway contributes to atrial fibrosis in an atrial fibrillation experimental model and patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 93 ] In addition, TGFbeta1 expression is specifically upregulated in patients with extensive low-voltage areas undergoing ablation. [ 94 ] Serum TGF-beta1 has been shown to be an independent risk factor for AF recurrence after ablation in both paroxysmal and persistent AF. [ 93 , 95 ] Interestingly, Kishima et al found lower concentrations of TGF-beta1 in patients with recurrence after ablation.…”
Section: Clinical Evaluation Of Myopathymentioning
confidence: 99%
“…Zhou et al reported that an increase in circulating microRNA served as SRM 35 . Transforming growth factor‐beta was specifically upregulated in intermediate monocytes in patients with progressed 36 . Previous studies have reported that SRM detected by LGE‐MRI is a strong and independent predictor of arrhythmia recurrence after CA 14,21,22 .…”
Section: Discussionmentioning
confidence: 99%